Livelihood of Street Children and Their Quality of Life: A Cross Sectional Study in Etawah District - K Kiran; Naresh Pal Singh; Dhiraj Kumar Srivastava; Ankita Sharma; Mahima Chandini (Medsci Publications, 2020)
Introduction: "Street children" is a term used to describe those kids who live and work in streets. Children are exposed to several hazards and catastrophe which lead them to vulnerable and pessimistic experiences. Their daily life and poor quality of life uncover them to various threats that makes them victims for drug trafficking, prostitution, organ trade and slavery. Material & Methods: A cross sectional study was conducted in Etawah city from May 2017 to Oct 2018. Street children aged 13-18 years, who live and/or work on streets of Etawah. Street children were looked for at identified hotspots of street children in Etawah city like market places, railway station, stalls/dhabas/hotels etc. and they were selected for the study by Snowball sampling. Information was extracted from face to face interview using pre-structured questionnaire. Results: Study enrolled 145 street children, 35% haven't attended school, 30% leave away from family. Street level vending, working in dhabas and mechanic assistant were common professions. Working children had poor quality of life. Conclusion: More than four fifth of the street children were working for their survival, street level vending, working in dhabas were common occupations involved. Quality of life was poor among working street children.